Effects of Heat Treatment on the Machinability of Cr-Ni Stainless Steels with Si and Mn Additives - Yaz, Mehmet; Koek, Metin; Turhan, Hueseyin (Carl Hanser Verlag, 2009)
In this work, the machinability of Cr-Ni austenitic stainless steels with Si and Mn additives was investigated based on tool life and tool wear by turning process without coolant on twelve different specimens in as-cast and heat-treated states. Metal removing process was carried out for four different cutting speeds using HSS cutting tools, while a cutting depth of 1.5 mm and a feed rate of 0.1 mm/min were kept constant. The effects of changes in microstructure with respect to addition elements and heat treatments on the tool wear and the hardness were examined. It was seen that the machinability for all of the specimens was not so good with the tools used. Although the hardness of the materials, which were as-casting, increased slightly with increasing the content of Cr and Ni addition elements, the machinability of these materials was not affected positively or negatively with respect to these elements. As heat treatments increased the hardness of the materials, the optimum tool lives were obtained in the machining of water quenched specimens. It was found that cutting speed was the most influential parameter on tool life.
Auswirkungen der Wärmebehandlung auf die Bearbeitbarkeit von nichtrostenden CrNi-Stählen mit Zusätzen von Si und Mn